Leptin-Mediated Transcriptional Regulation of Pomc in Hypothalamic Neurons - Hael, Clara Ercilia (2019)
Although it is well accepted that the adipostatic hormone leptin activates Pomc expression inhypothalamic neurons, the mechanisms controlling this interaction remain unexplored. In thebrain, leptin binds to the long form of the leptin receptor stimulating the intracellularphosphorylation of STAT3 which acts as a transcription factor of several genes by acting on STAT3binding motifs. We have detected that the neuronal Pomc enhancer 1 (nPE1) contains twocanonical STAT3 binding motifs (5?-TTCCNGGAA-3?) which are highly conserved in mammals. Tochallenge the hypothesis that these sites participate in leptin´s induced Pomc expression wegenerated mutant mice lacking both STAT3 sites from nPE1 using CRISPR/Cas9 technology. Tomaximize leptin´s effect on hypothalamic Pomc expression we previously reduced circulatingleptin levels using two different experimental strategies. Our first approach was to study the effectof refeeding on mice previously fasted for 24 h and analyze body weight variations andhypothalamic Pomc mRNA levels. Our preliminary results indicate a greater weight loss in micelacking STAT3 sites after fasting and a more rapid regain of previous body weight. The secondapproach involves crossing nPE1(STAT3-less) mice with leptin-deficient (ob/ob) mice. Furtherprogress of these experiments will give us the possibility to evaluate the implication of STAT3binding sites in the regulation of hypothalamic expression of POMC induced by leptin.